Bibliometric analysis of research trends on factors affecting older adults with mild cognitive impairment - Yang, Lei; Yang, Rushi; Wang, Bo; Liu, Tiantian; Wang, Ziyi (Frontiers in Neurology, 2024)
Background In recent years, the problem of cognitive impairment in the elderly has become increasingly prominent. Understanding the research trend of influencing factors of mild cognitive impairment, and provide reference for medical staff to early screening of the elderly with mild cognitive impairment. Objective Through the visual analysis of the influence factors of the elderly with mild cognitive impairment, the current research status was discussed. Methods The relevant literature in the field of influencing factors of mild cognitive impairment in the elderly included in the Web of Science core collection database from 2013 to 2022 was searched. Using software such as Cite Space and VOS viewer to visually analyze literature citations, country, keywords, and development trends. Results A total of 547 relevant literatures were included, and the number of publications showed an increasing trend in the past ten years. The United States ranked first in both the number of published papers (157) and centrality (0.34), and the United States and China had a greater influence on the influencing factors of mild cognitive impairment. Alzheimer’s disease, cognitive decline, the elderly, risk factors, are the research hotspot in this field. Conclusion Cognitive decline will affect the autonomy of the elderly. Cognitive frailty, MRI is the forefront of MCI research, to understand the research hotspots and frontiers in this field, to conduct early screening and intervention guidance for people with mild cognitive impairment, so as to delay the occurrence of Alzheimer’s disease, and reduce the pressure on family caregivers and society.